The Influence of Compensation and Organizational Commitment on Employees' Turnover Intention at PT Ruang Raya Indonesia (Ruangguru) West Kalimantan Regional Office - Satrio Nugroho; Arninda Arninda (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study examines the impact of Compensation and Organizational Commitment on employees' Turnover Intention at Ruangguru. The research utilizes a quantitative approach with 58 respondents from various departments within the organization. Data were analyzed using multiple linear regression, with normality, linearity, and multicollinearity tests conducted to ensure the validity of the results. The findings reveal that both Compensation and Organizational Commitment have a significant influence on Turnover Intention, with Compensation being the more dominant factor. Higher compensation increases the likelihood of employees considering leaving the organization if they feel inadequately compensated, while stronger Organizational Commitment reduces Turnover Intention. These results suggest that organizations should focus on offering competitive compensation and fostering a strong commitment to minimize turnover intentions and improve employee retention.